치약선택기준에 따른 구매만족, 재구매 의도 및 권유 의사 분석 - 한예슬; Ye Seul Han; 이지은; Ji Eun Lee; 문학진; Hak Jin Moon; 임순연; Soon Ryun Lim; 조영식; Young Sik Cho (Chiwisaeng gwahakoeji, 2015)
본 연구는 치과대학병원 구강관리용품 전시실에서 치약을 재구매한 고객을 대상으로 조사하여 치약에 대한 고객의 선택기준이 구매 만족도와 재구매 의사 및 권유 의사에 미치는 영향을 파악하기 위하여 시행하였다. 조사대상자는 248명이었으며, 연구 결과는 다음과 같다. 치약 선택기준 ‘맛’, ‘가격’, ‘브랜드’, ‘기능’, ‘디자인’ 과 만족도는 양의 상관관계를 나타냈다. 또한 구매 만족도와 재구매 의도 및 권유 의사는 양의 상관관계를 보였다. 고객이 치약을 구매할 때 선택하는 기준에서 ‘맛’, ‘가격’, ‘브랜드’, ‘기능’ 요인이 구매 후 만족도가 높은 것으로 나타났다. 그 중 ‘기능’ 요인이 만족도에 가장 영향력이 큰 것으로 나타났으며, ‘브랜드’, ‘맛’, ‘가격’ 순으로 영향력이 있었다. 고객의 만족도는 재구매 의도 및 권유 의사에 영향을 미치는 것으로 나타났다. 치약 제품에 대해 만족한 경우 재구매를 하겠다는 의도를 보였으며, 타인에게 본 제품을 추천할 의사가 있다는 의견이 나타났다. 본 연구의 종합적인 결과 치약을 구매하는 선택 기준으로는 치약의 기능 및 효능이 가장 큰 영향력을 보였으며, 치약제품의 브랜드, 맛이나 느낌, 가격에 따라 구매 만족감을 보였다. 또한 치약의 포장 및 디자인은 치약 선택 시 큰 기준점으로 작용하지 않았다. 선택한 치약에 만족한 경우 재구매의사가 높았으며, 타인에게 권유하려는 의사 또한 높았다. 따라서 치과계와 치약 제조회사는 치약에 대한 많은 정보들을 고객과 함께 공유할 수 있는 시스템을 개발을 할 필요가 있으며, 치약뿐만 아니라 구강관리용품에 대한 제품 정보나기능, 맛에 대해 지속적으로 연구하고 개발하는 것이 필요하다고 사료된다. The purpose of this study was to understand the buying behavior characteristics of the customers. Also, it was intended to provide information to provide companies marketing strategy. The criteria of purchasing toothpaste was to try to understand the impact on satisfaction, recommendation and repurchase Intention. The study was surveyed 248 customers who re-buy the toothpaste in oral care products showroom at university dental hospital. Statistical analysis was performed using PASW Statistics 18.0 and AMOS 18.0 at the 5% significance level. The results were as follows: ‘Flavor’, ‘Price’, ‘Brand’, ‘Function’, ‘Design’ of toothpaste and satisfaction showed a positive correlation. Satisfaction and repurchase intention, Recommendation showed a positive correlation. Selection criteria that affect the satisfaction when customers buy toothpaste, ‘Function’ was the greatest and others became the order of the ‘Brand’, ‘Flavor’, ‘Price’. Satisfaction affect the recommendation and repurchase Intention. If customers are satisfied with the toothpaste products, showed the Repurchase Intention, have shown opinion that is willing to recommend this product to others. Therefore, dentistry and manufacturers of toothpaste must share a lot of information about toothpaste with customers. Also, information, function, flavor of toothpaste as well as other oral care product, It will be a needed the continuing research and development.